Resolving Conflicts During Confiscation of Machine Data Carriers and Computer Technology Facilities - Nikolay Anatoleevich Ivanov (Сибирское юридическое обозрение, 2011)
The article takes up the ways of resolving conflicts that arise when the confiscation of machine data carriers and computer technology facilities take place at commercial enterprises during criminal investigation.